A novel orange-colored bimolecular fluorescence complementation (BiFC) assay using monomeric Kusabira-Orange protein - Yuta Fujii; Ayaka Yoshimura; Yutaka Kodama (BioTechniques, 2018)
The bimolecular fluorescence complementation (BiFC) assay was developed as a tool for the visualization of protein–protein interactions in living cells. To date, many types of BiFC systems with distinct colors have been developed. Most of the colors in the visible spectrum have been used in BiFC assays, with the exception of orange. In this study, we developed an orange-colored BiFC system using the Kusabira-Orange (KO) protein from the stony coral Fungia concinna. To obtain bright BiFC fluorescence, we compared fluorescence intensities of two monomeric KO variants (mKO1 and mKO2) and identified mKO2 as brighter than mKO1. The optimal split site for mKO2-based BiFC was defined by a comparative analysis of complementation efficiency and a signal-to-noise ratio. The resulting mKO2-based BiFC system successfully demonstrated protein dimerization in plant cells as a model experiment. The novel mKO2-based BiFC system will expand the possibility of multicolor BiFC analysis.